Mucoadhesive in-situ Gel Formulation for Vaginal Delivery of Tenofovir Disoproxil Fumarate - Patel, Anita Prahladbhai; Patel, Jayvadan K. (Indian Journal of Pharmaceutical Education and Research, 2020)
Introduction: Tenofovir disoproxil fumarate is an anti-retroviral medicine which belongs to microbicides class being formulated for a woman instigated technique of prevention of the human immunodeficiency virus infection. The objective of the present investigation is to prepare thermosensitive mucoadhesive in-situ vaginal gel of Tenofovir disoproxil fumarate that can present pre-exposure prophylaxis against human immunodeficiency virus in addition to providing excellent spreading as well as coating of the vagina, forming the therapy more effectual and bring about extended effect. Materials and Methods: The vaginal in-situ gel of Tenofovir disoproxil fumarate was prepared using thermosensitive polymer poloxamer 407 and mucoadhesive polymer carbopol 934 by a cold method. It was characterized for drug-excipient compatibility, viscosity, gelation study, gelling capacity, in-vitro drug release study, stability study and Hen’s Egg Test-Chorioallantoic Membrane assay. Results and Discussion: Drug excipient compatibility study displayed that there is no interaction between drug and excipients. Formulation F2 was found as the most appropriate formulation on the basis of the evaluation parameters, as it displayed the preferred properties. The work of adhesion values was used as parameters for comparison of mucoadhesive performance and it was found as 0.324 ± 0.036 N. Hen’s Egg Test-Chorioallantoic Membrane test showed that the formulation is nonirritant to the vaginal mucosa. Formulation F2 was subjected to accelerated stability studies at 40°C ± 2°C /75% RH ± 5% RH for 6 months. The results showed that it stayed steady for 6 months. Conclusion: It can be concluded that the development of a tenofovir in-situ vaginal gel which may offer effective and sustained protection against human immunodeficiency virus infection.
Keywords: Antiretroviral drug; Thermosensitive; Mucoadhesive; in-situ gel; Non-irritant